A call to action for human experience - Jason Wolf (The Beryl Institute, 2021)
As we open the 8th volume of Patient Experience Journal (PXJ), we all stand in a world much different than we did just a year ago. A year ago we were in the height of crisis, facing unknowns and uncertainty. We didn’t know if we were tackling an issue that was weeks, months or years in front of us. We were truly not even sure what tomorrow might bring. As I shared in opening Volume 7, we were already experiencing something special in the midst of real tragedy. We were seeing light peeking through heavy clouds. I opened that issue sharing, “At the heart of healthcare, we are human beings caring for human beings, [and] at the heart of the actions and efforts of so many at this time of crisis, we find the true essence of the humanness of healthcare. Yes, the clinical excellence at healthcare’s roots will ensure we save lives, but the efforts we are seeing to elevate the human experience now will ensure we honor those lives through and beyond this crisis as well.” While this crisis challenged us in ways we have never seen, it equally highlighted the realities we knew already existed but had yet to fully address. The opportunity this reveals provides a significant moment of choice: do we perpetuate our efforts of the past or do we bend the arc for a new future? We are at a unique moment for our community, for our world…one we must not miss. Please join us in transforming the human experience by sharing your ideas via PXJ, taking action in your organizations, working to impact the communities in which you live and work, by signing and acting on the Declaration for Human Experience. That is the least we can do for one another in an industry, and I dare say a world, where we must forever be human beings caring for human beings. We are the human experience, and now is the time to act.